Research on the Effect of Pinduoduo’s Agricultural Support and Poverty Alleviation in China - Zeng, Dongxia; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
Upon the implementation of the 12th Five-Year Plan, our government gives great impetus to the poverty alleviation via Internet plus agriculture and e-commerce. With the popularization of rural Internet and the improvement of e-commerce related infrastructure, the project has achieved certain results. Pinduoduo is a typical case company of e-commerce poverty alleviation, because it actively responds to the national call, vigorously participates in the cause of poverty alleviation and agricultural support, uses its own advantages of e-commerce sales, integrates the entire chain including the source purchase of agricultural products, logistics distribution, consumer terminal services, and solves the problems of agricultural production and sales in remote mountainous areas, so as to support the local agricultural development, improve the local economic level, and give assistance to the government eliminate the poor population. This paper takes Pinduoduo as a case analysis object to analyze the motivation, mode and effect of poverty alleviation through Pinduoduo, and puts forward conclusions and suggestions based on personal research results.